Research on throughput maximization for intelligent reflecting surface assisted dual-hop relay wireless powered communication network - Zhen YANG; Xuan FENG; Bin LYU (Tongxin xuebao)
To improve the energy and information transmission efficiency of relay-based wireless powered communication network (WPCN), a two intelligent reflecting surface (IRS) assisted dual-hop relay wireless transmission scheme was proposed.In particular, IRS1 and IRS2 were deployed between the base station (BS) and hybrid relay node (HRN), and between the HRN and users, respectively, which could improve the efficiency of energy transfer from the HRN to users, data transmission from users to the HRN and data forwarding from HRN to BS.To maximize the system throughput, an optimization problem was formulated, where the time scheduling of energy, information transmission and forwarding, the phase shifts of IRS, and the delivered power of users were jointly optimized.To address non-convexity of the formulated problem, an efficient alternating optimization algorithm was proposed and the sub-optimal solution was obtained.In addition, the convergence and computational complexity of the proposed algorithm were analyzed.Numerical results verify that IRS can effectively improve the throughput of WPCN based on relay.In addition, compared to the benchmark schemes, the proposed optimal transmission scheme can significantly improve the system performance in terms of throughput.